UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE COOPERATIVE SCRIPT PADA SISWA KELAS VIIIA SMP N 1 BINANGUN CILACAP - Ruminah Ruminah; AA Sujadi (Universitas Sarjanawiyata Tamansiswa, 2014)
Cooperative script method is oneÂ method to improve studentâ€™s interest in learning and students' achievement. This research is Classroom Action Research (CAR). The subject of the research is eightÂ grade students of Junior high school Binangun Cilacap. It is conducted in two cycles, each cycles consists of planning, acting, observing and reflecting. The data revealed from observation, questionnaire, test and documentation. The result of the research was there are increasing student interest and students' achievement. This forum can be teachers' reflection to be much better in mathematic teaching and learning.